Detection of bacterial pathogens using home oropharyngeal swab collection in children with cystic fibrosis. Issue 7 (26th April 2021) - Lenhart‐Pendergrass, Patricia M.; Anthony, Meg; Sariyska, Sabina; Andrews, Ashley; Scavezze, Heather; Towler, Elinor; Martiniano, Stacey L.; Hoppe, Jordana E.; Zemanick, Edith T.
Abstract: Background: Collection of respiratory cultures for airway microbiology surveillance is an essential component of routine clinical care in cystic fibrosis (CF). The COVID‐19 global pandemic has necessitated increased use of telehealth, but one limitation of telehealth is the inability to collect respiratory specimens. We initiated a protocol for at‐home collection of oropharyngeal (OP) swabs from children with CF. Methods: Home respiratory specimen collection was offered during telehealth encounters. Home OP swab kits were sent to participating families via mail with instructions for collection and return. Specimens were returned by overnight shipping or dropped off at a hospital lab for processing and culture. We evaluated demographic data and compared culture results from the home‐collected specimen to the most recent specimen collected in clinic. We also tracked the frequency of newly identified Pseudomonas aeruginosa . Results: Home OP swab kits were sent to families of 33 children with CF (range 1.5–19 years). OP swab kits were successfully returned from 19 children (range 1.5–19 years). One or more CF pathogens grew from 79% of the specimens. For four individuals, the home collected specimen demonstrated the new growth of P. aeruginosa . Conclusions: Home collection of OP swabs for bacterial culture is feasible in children with CF across a range of ages. Most home‐collected specimens demonstrated growth of one or more CF pathogens and results were similar to recent in‐clinic specimens, suggesting acceptable sample collection technique. Anti‐pseudomonal therapy was initiated for four children based on the growth of P. aeruginosa from the home respiratory specimen.